Exploration of Customer Interest in Using M-Banking Facilities at PT BRK Syariah Pekanbaru - Khansa, Jeslyn Faiza; Azmi, Zul (JAAF (Journal of Applied Accounting and Finance), 2025)
This research aims to explore what factors encourage BRK Syariah Pekanbaru customers' interest in using M-Banking facilities. We conducted a field survey to obtain data. By using a qualitative descriptive approach, data collected by interview method, then collected, classified, and tested to be further analyzed. The results showed that the services available in the BRK Syariah Mobile application feature have attracted customers in transacting easily because by using the BRK Syariah Mobil application users can make transactions anywhere and anytime without having to visit BRK Syariah offices and ATM machines. However, the BRK Syariah Mobile application application still has to improve services by providing cash deposit and withdrawal features so that customers can make money deposit and withdrawal transactions without using an ATM card and the application must also continue to be improved in the network so as to minimize the occurrence of an erroneous BRK Syariah Mobile application.